Anti-VEGF therapies in the treatment of choroidal neovascularisation secondary to non-age-related macular degeneration: a systematic review. Issue 4 (3rd May 2015) - Stuart, Arabella; Ford, John A; Duckworth, Susan; Jones, Colin; Pereira, Augustine
Abstract : Objectives: The aim of this study is to systematically review the evidence for anti-vascular endothelial growth factor (VEGF) therapy in choroidal neovascularisation secondary to conditions other than age-related macular degeneration. Data sources: MEDLINE, MEDLINE in-process, EMBASE and CENTRAL databases and conference abstracts were searched (from inception to Jan 2014). Study eligibility criteria, participants and interventions: Randomised and non-randomised comparative studies with follow-up of at least 6 months were included and were used to assess clinical effectiveness. Study appraisal and synthesis method: Risk of bias was assessed using the Cochrane risk of bias tool and modified Newcastle-Ottawa Scale. Meta-analysis was not possible due to methodological heterogeneity. Results: 16 studies met the inclusion criteria (1091 eyes; 963 pathological myopia, 74 other conditions). There was large variation in risk of bias across studies. An improvement in best-corrected visual acuity in anti-VEGF arms over comparators was reported in all studies. The proportion of patients improving by at least 15 letters in anti-VEGF arms ranged from 27.3% to 70%. There were no significant differences between bevacizumab and ranibizumab. Limitations: Owing to the rarity of choroidal neovascularisation secondary to conditions other than age-related macular degeneration or pathological myopia, there are unlikely to ever be sufficiently powered trials in these populations. Conclusions: Bevacizumab and ranibizumab appear to be effective in improving visual acuity for patients with choroidal neovascularisation secondary to conditions other than age-related macular degeneration. The evidence base is strongest for choroidal neovascularisation secondary to pathological myopia, however, based on current evidence and likely pharmacological pathways, clinicians should consider treatment with either bevacizumab or ranibizumab for rarer causes.